1992
DOI: 10.1007/bf00848326
|View full text |Cite
|
Sign up to set email alerts
|

The relation between stress and disease activity in rheumatoid arthritis

Abstract: This study investigated the relation between stress and current disease activity in rheumatoid arthritis (RA). During a routine clinic appointment, subjects were given ratings of global disease status by their physicians and completed self-report measures of major stress and minor stress. In addition, each subject's erythrocyte sedimentation rate was taken. After controlling for disease severity and major stress, minor stress accounted for a significant amount of the variance in inflammation level. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 14 publications
2
47
1
4
Order By: Relevance
“…However, a stress-induced enhancement of immune function could also be detrimental if the immune response were directed against an innocuous (e.g., poison ivy, nickel in jewelry, or latex) or autoimmunogenic antigen. This hypothesis could explain the well known stress-induced exacerbation of autoimmune diseases (38)(39)(40). Moreover, we have shown that chronic stress (1) and hormonal conditions that mimic chronic stress suppress immune function.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, a stress-induced enhancement of immune function could also be detrimental if the immune response were directed against an innocuous (e.g., poison ivy, nickel in jewelry, or latex) or autoimmunogenic antigen. This hypothesis could explain the well known stress-induced exacerbation of autoimmune diseases (38)(39)(40). Moreover, we have shown that chronic stress (1) and hormonal conditions that mimic chronic stress suppress immune function.…”
Section: Discussionmentioning
confidence: 65%
“…Another paradoxical observation is that, on the one hand, stress is thought to suppress immunity and increase susceptibility to infections and cancer (8,10,(35)(36)(37). On the other, it is thought to exacerbate inflammatory diseases (38)(39)(40), like psoriasis, asthma, and arthritis, which should be ameliorated by a suppression of immune function. Keeping these considerations in mind and based on our initial observations on the effects of stress and of the circadian corticosterone rhythm on leukocyte redistribution in the body (12,13), we showed that stress has bidirectional effects on immune function, such that acute stress is immunoenhancing, whereas chronic stress is immunosuppressive (1, 13, 15).…”
Section: Discussionmentioning
confidence: 99%
“…Second, on the one hand, stress is thought to suppress immunity and increase susceptibility to infections and cancer (7,9,(64)(65)(66), while on the other, it is thought to exacerbate inflammatory diseases like psoriasis, asthma, and arthritis (which should be ameliorated by a suppression of immune function) (67)(68)(69)(70)(71). The finding that depending on specific physiologic conditions stress can either enhance or suppress immune function may help reconcile these paradoxical observations (1,2).…”
Section: Dhabhar Et Almentioning
confidence: 99%
“…FMS is more prevalent in women than in men (7:1) [3]. FMS patients report high levels of stressful life events [4] and daily nuisance [5,6] and frequently attribute the onset of their illness to stress, emotions, or trauma [7]. A recent study [8] on healthy subjects has also shown that psychological stress of their living state and work-associated stress persuade them toward high levels of stress.…”
Section: Introductionmentioning
confidence: 99%